REKRUTMEN, SELEKSI DAN PENEMPATAN DALAM PERSPEKTIF ISLAM - NILA MARDIAH (Universitas Islam Negeri Imam Bonjol Padang, 2016)
The research theme is the concept of business according to Islamic economics. The research objective is: to analyze recruitment, selection and placement according Islam. Research is the study of literature. Islam is the Religion of Allah. The rules of Islam come from God. God has sent down Al-Qur'an as a guidance to the ummah of Islam in the running of every aspect of life. The hadith is also used as the basis of muslims. So also the thing with the Islamic concept of human resource management. This paper describes how the Islamic perspectiveregarding the process of recruitment, selection and placement of human resources. How the process and implementation of recruitment, selection and placement in Al-Quran and Hadith to be guidelines for muslims.